EFFECT OF SPRAYING WITH DIFFERENT CONCENTRATION OF LICORICE EXTRACT AND PLANT DENSITIES IN GROWTH AND YIELD OF SORGHUM BICOLOR L. - & Al-Ani, Al-Mohmadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field experiment was condueted at the experimental Farm, College of Agriculture University of AL-Anbar in replace location (Abu-Gheaib) in spring season of 2017. While in Fall season it was applied at AL-saqluwiya-Anbar Province 10 km west north of Falluga city to study the effect of four levels of licorice extractor (Glycyrrhiza glabra L.) (0,2,4 and 6) g.L-1 water and three (53,333, 66,666 and 88,888 plant) plant.ha-1. On growth and grain yield of Sorghum cv. Rabih. The experiment was applied using R.C.B.D. arranged in split plots with three replications. levels of plant densities were used as main-plot, while licorice extractor were used as sub-plot. Foliar application of licorice extractor was applied during vegetative growth. The results showed that, high plant density (88888) plant.h-1 significantly increase plant height and leaf area index, while most of traits were not significantly influenced by plant density including grain yield. Results revealed that foliar application of licorice extractor with 2,4,6 g.L-1 of water significantly influenced grain yield in spring season compane with control treatment and it is amounted to (9.62, 9.55 and 9.78) t.h-1 respectively. There were significant interaction between Licorice extractor and plant density in spring and fall season in grain yield. The higher grain yield of 10.31 and 10.33 t.h-1 were obtained when sorghum plants were sowing at hight density and sprayed with Licorice extractor at level 4 g.L-1 respectively